New and interesting species of the genus Muelleria (Bacillariophyta) from the Antarctic region and South Africa - Van De Vijver, Bart; Mataloni, Maria Gabriela; Stanish, Lee; Spaulding, Sarah A. (Phycologia)
During a survey of the terrestrial diatom flora of some sub-Antarctic islands in the southern Indian and Atlantic Oceans and of the Antarctic continent, more than 15 taxa belonging to the genus Muelleria were observed. Nine of these taxa are described as new species using light and scanning electron microscopy. Comments are made on their systematic position and how they are distinguished from other species in the genus. Additionally, two previously unrecognized taxa within the genus were discovered in samples from South Africa. One of these, Muelleria taylorii Van de Vijver & Cocquyt sp. nov., is new to science; the other, Muelleria vandermerwei (Cholnoky) Van de Vijver & Cocquyt nov. comb., had been included in the genus Diploneis. The large number of new Muelleria taxa on the (sub)-Antarctic locations is not surprising. Species in Muelleria occur rarely in collections; in many habitats, it is unusual to find more than 1-2 valves in any slide preparation. As a result, records are scarce. The practice of "force-fitting" (shoehorning) specimens into descriptions from common taxonomic keys (and species drift) results in European species, such as M. gibbula and M. linearis, being applied to Antarctic forms in ecological studies. Finally, the typical terrestrial habitats of soils, mosses and ephemeral water bodies of most of these taxa have been poorly studied in the past. Fil: Van De Vijver, Bart. National Botanic Garden Of Belgium; Bélgica Fil: Mataloni, Maria Gabriela. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Stanish, Lee. University of Colorado; Estados Unidos Fil: Spaulding, Sarah A. University of Colorado; Estados Unidos